The structural and the functional aspects of intercellular communication in iPSC-cardiomyocytes - Kiss, Eva; Fischer, Carolin; Sauter, Jan-Mischa; Sun, Jinmeng; Ullrich, Nina D. (International journal of molecular sciences, 2022)
Recent advances in the technology of producing novel cardiomyocytes from induced pluripotent stem cells (iPSC-cardiomyocytes) fuel new hope for future clinical applications. The use of iPSC-cardiomyocytes is particularly promising for the therapy of cardiac diseases such as myocardial infarction, where these cells could replace scar tissue and restore the functionality of the heart. Despite successful cardiogenic differentiation, medical applications of iPSC-cardiomyocytes are currently limited by their pronounced immature structural and functional phenotype. This review focuses on gap junction function in iPSC-cardiomyocytes and portrays our current understanding around the structural and the functional limitations of intercellular coupling and viable cardiac graft formation involving these novel cardiac muscle cells. We further highlight the role of the gap junction protein connexin 43 as a potential target for improving cell-cell communication and electrical signal propagation across cardiac tissue engineered from iPSC-cardiomyocytes. Better insight into the mechanisms that promote functional intercellular coupling is the foundation that will allow the development of novel strategies to combat the immaturity of iPSC-cardiomyocytes and pave the way toward cardiac tissue regeneration.
Gesehen am 24.05.2022